The Potential of Food By-Products: Bioprocessing, Bioactive Compounds Extraction and Functional Ingredients Utilization - Verni, Michela; Casanova, Federico (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The pressure upon natural resources and the increasing awareness of the necessary transformation of the global food system are driving the quest of both academia and industry towards more sustainable approaches. Sustainability in the agro-food sector begins with the valorization of food industry waste and side streams, products with an extremely high intrinsic value but often discarded because unfit for further processing that meet consumers expectations. Apart from their use as feed, a more practical solution responding to the modern vision of circular economy must be sought. Indeed, several processes can guarantee that the potential of food industry by-products is fully unleashed, generating high-value ingredients while ensuring nutritional quality. In this framework, this Special Issue included the most recent advances in the valorization of food by-product (of both animal and plant origin), from extraction to bioprocessing, including their application in a variety of food-related industries throughout the entire food supply chain.